Investing in the concepts of Al-Ghadami’s cultural criticism in approaching contemporary poetry (Reading in the implicit pattern for Muthaffar AlNawab ) - hechaichi, siham (El Omda in Linguistics and Discourse Analysis, 2025)
Cultural criticism is one of the most important branches of contemporary critical theory. Its value is reflected in the comprehensiveness and diversity of its approaches, which, have proven to be effective in analyzing literary and non-literary discourses, away from their artistic and aesthetic characteristics, thus revealing details of their oppositions, complexities, and intellectual dimensions. The latter is done according to systematic mechanisms based essentially on linking these speeches to their multiple cultural patterns and interpreting them on the basis of ideological, historical, psychological, social, and all that the human culture system encompasses. This article explores the implicit political patterns in the poetry of Muthaffar al-Nawab in light of the theory of cultural criticism since his poems are teeming with the meanings of revolutionary anger, political struggle, incitement, resistance, and commitment, all of which are scattered in the folds of his poems nicknamed the smuggled poems.